Clinical Predictors of Functional Disability in Knee Osteoarthritis: Risk Stratification Approach as Implications of Nursing Practice - Yannis, Nafi; Tanjung, Dudut; Dedi Ardinata; Tasrif Hamdi; Nur Asnah Sitohang (Caring: Indonesian Journal of Nursing Science, 2025)
Osteoarthritis (OA) of the knee is one of the most common musculoskeletal disorders and a leading cause of disability in the elderly. The severity of osteoarthritis can be assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), which is a widely used tool to measure pain, stiffness, and physical dysfunction in patients with OA. This study aimed to analyze the relationship between the demographic and clinical characteristics of patients with knee osteoarthritis and their WOMAC scores. The study used a quantitative, cross-sectional observational design. The relationship between functional disability (measured by the WOMAC score) and various factors was analyzed. The independent variables included age, sex, occupation, body mass index (BMI), OA grade, and duration of OA to the WOMAC score. Significant correlations were found between the WOMAC score and both OA grade (p=0.049) and OA duration (p=0.030). Furthermore, the multiple linear regression analysis revealed that OA duration (p=0.038) and OA grade (p=0.036) were significant predictors of the WOMAC score, collectively explaining 13.0% of its variance (R² value = 0.130).  The findings of this study indicate that OA grade and duration of illness are significant predictors of the level of disability as measured by the WOMAC scores. OA levels and disease duration were the primary predictors of functional disability, explaining 13.0% of the WOMAC score variance. Nursing interventions should focus on risk stratification based on these clinical markers, prioritizing early intervention for newly diagnosed patients, irrespective of their age or BMI.